Pengaruh Integrasi Media Dopesen pada Model Student Facilitator and Explaining terhadap Kemampuan Pemahaman Konsep Siswa Kelas V SD - Wahyu Tyas Utami; Lisa Virdinarti Putra (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine the effect of the Student Facilitator And Explaining learning model assisted by Dopesen media on the conceptual understanding ability of fifth grade elementary school students. The type of research used is Quasi Experimental Design with Nonequivalent Control Group Design. The population in this study were all students of Ungaran 02 Elementary School. The sample used in this study was non-probability sampling with purposive sampling technique. The sample of this study was fifth grade of Ungaran 02 Elementary School. Data collection techniques used were test techniques and non-test techniques. The test technique used pretest and posttest while the non-test technique used observation, questionnaires and documentation. Data analysis techniques with normality tests, homogeneity tests, independent sample t-tests and simple linear regression. The results of the study showed: (1) There was a difference in students' conceptual understanding abilities regarding the use of the Student Facilitator And Explaining model assisted by Dopesen media, with a significance value of 0.010 < 0.05 (2) There was an influence of the use of the Student Facilitator And Explaining learning model assisted by Dopesen media on students' conceptual understanding abilities with a significance value of 0.003 (<0.05).